The Role of the Volksraad in the Dutch East Indies Period - Simarmata, Diva Nancy Audissa; Simanjuntak , Duana Angel; Simarmata, Rendi Rianto; Sinaga, Rosmaida (Lembaga Riset Mutiara Akbar NOMOR AHU-0003295.AH.01.07 TAHUN 2021, 2024)
This article reviews the role of the Volksraad, the people’s representative body during the Dutch East Indies government. Through a historical overview, this article discusses how the Volksraad influenced Dutch colonial policy and its relationship with political dynamics and aspirations of indigenous people. Analysis was carried out on the role of the Volksraad in the context of colonial politics and social changes at that time. By understanding the role of the Volksraad, this article aims to provide insight into the political and social dynamics of the Dutch East Indies. The method used is literature with collect research materials in the form of books and relevant scientific articles. The results of the research show how the Volksraad was born and its role in the Dutch East Indies government in Indonesia